SIMBOL DAN PEMAKNAAN GERGA PADA RUMAH ADAT BATAK KARO DI SUMATRA UTARA - Fuad Erdansyah (Pascasarjana Institut Seni Indonesia Surakarta, 2011)
This research belongs to a field study, taken place in villages Lingga and Dokan Regency Karo. Generally, this research reveals the traditional values based on social-cultural background of Karo people, while particularly it reveals the meaning of ornament style in Batak Karo custom house called gerga. For that reason, the objectives of research are: (1) to describe the belief and kinship sistem underlying the gerga establishment in Karo custom house; (2) to describe the architectural components in Karo custom house consisting of: kitchen or floor crossbar, room, wall, facade, and roof platform; and (3) to reveal the symbolic meaning in gerga (ornament style). In order to achieve those objectives, the research method or procedure is required to determine the data source, both from the informant and custom house artifact completed with its style ornament. Techniques of collecting data used were from library study, observation, interview and documentation. The data was then analyzed based on the qualitative method using analytical interpretation with semiotic approach and batak karo rakut sitelu. Furthermore, the result of research shows that: (1) the belief and kinship sistem underlies the conception in establishing custom house and gerga; (2) the presence of custom house is the symbol of Karo people’s cosmology, as well as the birth place of kinship system called rakut sitelu; and (3) the symbolic meaning of gerga has denotative and connotative meaning orientation based on its pattern and motive containing the message both as the adoration and as the tenet for batak Karo people. From the result of research, it can be concluded that gerga contains the meaning relevant to the original belief influenceas well as indicates the megalithic culture development containing religious (sacred) values, norms or customs or tenets(semi-sacred) as well as containing aesthetical and ornamental (profane) values. However, Karo custom house has lost its sacred religious values because it starts to be abandoned by its people, and its existence is just as the past monument, while the gerga motive that was sacred and semi-sacred previously becomes now profane. This research is expected to enrich the cultural information and actualization through the messages obtained from symbol and sign system.Keywords: Gerga, symbol, sitelu rakut and custom house.